Pengaruh Gaya Kepemimpinan, Budaya Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Departemen Produksi CV. Gloria Tri Agung, Tulungagung) - Mia Novitasari; Abdul Kodir Djaelani; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Employee performance is one of the factors that influence the level of success of an organization. Employee performance can be measured if an employee or group of employees has performance criteria or parameters set by the company or organization. The purpose of this study was to determine the effect of leadership style, work culture, and work environment on employee performance at the Production Department employees of CV. Gloria Tri Agung, Tulungagung. The population in this study were production department employees at CV. Gloria Tri Agung, Tulungagung. The approach method uses a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to production department employees, totaling 116 respondents and using the SPSS analysis tool. The results of the study show that leadership style, work culture and work environment simultaneously have a significant effect on employee performance. Partially, leadership style and work culture have a significant effect on employee performance, while the work environment has no significant effect on employee performance. Keywords: Leadership Style, Work Culture, Work Environment, Employee Performance.